Fair-Weather Abusers? Civil War Dynamics and the Onset of State-Sponsored Violence. - Keels, Eric; Greig, J Michael (International Studies Quarterly, 2023)
Despite decades of rigorous research on the use of government-sponsored violence in armed conflicts, there remains significant uncertainty as to when and where leaders choose to target civilians in war. We argue that the variation in the use of state repression is explained in part by how soldiers perceive battlefield gains by rebel forces. Specifically, while strong opposition forces are often a necessary condition for elites convincing agents to engage in state-sponsored brutality, this is modified by the soldiers' beliefs surrounding the outcome of the war. If government soldiers believe that rebels are likely to win the war, we posit that they will likely shirk orders to target civilians, fearing post-war accountability. We test this argument by examining subnational variation in battlefield dynamics and the use of government one-sided violence from 1992 to 2010.